COVID‐19 herd immunity in Lebanon: Challenges and prospects - Christopher Maatouk; Orestis Germanos; Anna‐Maria Aad; Georges Gandour; Julian M. A. Buban; Ralph Maatouk; Michelle Zeina; Shyam Sundar Budhathoki; Don Eliseo Lucero‐Prisno III (Wiley, 2024)
Abstract COVID‐19 hit Lebanon at the worst time, amid an economic downward spiral and national protests regarding living conditions and political corruption. The first case was found on February 21, 2020, and the first batch of vaccines arrived on March 24, 2021. Although neither natural infection nor mass vaccination truly provided herd immunity, the latter was a more effective way to handle the pandemic, and Lebanon fell short on that path. During the pandemic, a myriad of factors complicated its response to the virus. Thanks to the COVAX program, the country received 1086,720 doses donated and 1626,390 deliveries. All in all, over 5.8 million doses have been administered. A total of 2.74 million people received at least one dose, and 2.4 million had a complete primary vaccination series. However, around 98% of the population were infected with the virus. Issues that stopped the vaccination campaigns include a lack of trust in government officials and news media, leading to false information propagating and remaining unchallenged online. Other factors include the economic collapse, which led to the Lebanese currency losing over 98% of its initial worth. Some Lebanese people might find themselves either unable to reach proper health facilities or unwilling to adopt the narrative pushed by the political elite. Poverty also worsened affected infected individuals' prognosis and mortality. A bigger emphasis must be put on reaching individuals with disabilities or in low‐income areas, as they were the most affected by the pandemic. Problems these communities face include the lack of funding for special education schools and the lack of accessibility to medical information promoted by the government. Lebanon must learn from the issues that arose during this pandemic and focus on fixing them in advance to prepare for any other health emergency that might turn up in the future.